Increasing the strategic role of HR: the importance of macro-economic conditions. Issue 2 (12th March 2018) - Morris, Adam
Abstract : Purpose: The purpose of this paper is to introduce notions for increasing the strategic position of the HR function by outlining the influence that macro-economic trends play on the role of the function and the success of its initiatives. The main focus is on how HR can over time change with economic cycles to add tangible value and drive strategic conversations. Design/methodology/approach: This argument is split into three sections: the importance of strategic considerations for change, macro-economic trends and HR, and HR's increased input to business strategy. It looks at the work of key theorists in change management, analyzes the history of HR and develops these arguments into conclusions about how to improve HR's strategic role. Findings: Key theories of change management demonstrate that strategy is critical to the success of change projects. This means encompassing both internal and external factors affecting a business. By examining the historical development of HR it is clear to see that macro-economic trends are a significant external factor that is not often investigated by HR. If HR can harness this information, they will be able to implement proactive initiatives and drive strategic conversations. Originality/value: The notions outlined in this paper identify a significant factor for the success of HR that is not often investigated by the function, allowing HR to implement more effective initiatives at optimal times.